Océan Indien et Océan Austral - Iles Eparses / Service hydrographique de la marine . 1940 - France. Service hydrographique de la marine; (1953)
Remplacement Janvier 1952. Corr. 1953 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in purple.; Groupe: Marion - Prince Edouard -- I. Marion, Crique Jeannel -- Groupe: Ambsterdam - Saint-Paul.; Includes 3 coastal profiles Color;